Never again Sabra-Shatila! (International Seminar on the Sabra-Shatila Massacre, 1983)
Colour drawing of bloody bayonet and soldier's boot among children's toy blocks laying on the floor Poster advertising the International Seminar on the Sabra-Shatila Massacre, held in Athens, September 16-18th, 1983 PO-1325